Methods for Obtaining Calcium Nitrate - Z. T. Ruzieva; F. I. Kudratov (Research Parks Publishing LLC, 2022)
A detailed analysis of the physical and chemical properties of nitrite and sodium nitrate has been made, which must be taken into account when it is used in certain sectors of the national economy. An analysis of the literature data showed that the most acceptable method is the determination of sodium nitrite by titration. This method of analysis meets the requirements of expressiveness, accuracy, sensitivity, and the possibility of automating the control process under production conditions.